Bridging the Gap between Population Needs and Barriers into Onsite Clinic Use. (September 2016) - Ostovari, Mina; Yu, Denny; Xie, Shan; Ye, Qing; Katare, Bhagyashree; Adibuzzaman, Mohammad; Musselman, Kenneth J.; Nateghi, Roshanak; Shield, Cleveland G.; Yih, Yuehwern
Providing occupational care in worksite clinics has been a common service offered by employers specifically among companies with high incidence of hazardous events. In recent years, onsite clinics have expanded their services to non-occupational care. Various types of employers such as universities have started providing care to employees and their dependents through onsite clinics. The purpose of this pilot study is to assess health claim data of a self-insured public university to identify patient-population factors, such as demographic and health conditions, that may influence the utilization of health services offered by the onsite clinic. Common health services and health conditions were compared for patients using onsite clinic and for patients that choose to use offsite providers. Potential hypotheses based on the presented descriptive comparisons are proposed to further distinguish population health needs and potential barriers on onsite clinic usage. Preliminary findings and methodology in this pilot study can help improve healthcare services provided by onsite clinics and lead to more patient-centered healthcare delivery.